PENGARUH RETURN ON ASSETS (ROA) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PADA PT MANDOM INDONESIA TBK PERIODE 2010-2019 - Fadli, Achmad Agus Yasin; Suraya, Amthy (JAB (Jurnal Akuntansi & Bisnis), 2021)
This study aims to determine the factors that influence the share price of PT Mandom Indonesia Tbk. period 2010-2019. The variables in this study use two variables, namely the dependent variable (y) in this study the stock price. For the independent variable (x) in this study, the Retrun On Asset (x1) and Price Earning Ratio (x2). This research uses quantitative methods. The data used in this study are secondary data with 10 data samples from 2010-2019. Data collection was taken using documentation techniques sourced from the official website of PT Mandom Indonesia Tbk and the Indonesia Stock Exchange. The data that has been obtained, processed and analyzed so as to obtain a systematic picture and can be drawn conclusions. T test results for ROA tcount = 2.337 while ttable = 2.30600. So that tcount ≥ ttable with a significance of 0.049 ≤ 0.05 means that the Return on Assets (ROA) has a positive positive effect on stock prices. T test results for PER Tcount = 3.089 while Ttable = 2.36462. So tcount H ttable with a significance of 0.018 ≤ 0.05 means that the Price Earning Ratio (PER) has a significant effect on stock prices. For the F test obtained Fcount = 4,870 while Ftable = 4,46. So that the Fcount ≤ Ftable with a significant value of 0.047 ≤ 0.05 means that the Return On Assets (ROA) and Price Earning Ratio (PER) simultaneously have a significant effect on stock prices. In addition, it can be seen from the coefficient of determination (R Square) of 0.582, the value is equal to 58.2%, which means the variable Retrun On Asset (ROA) and Price Earning Ratio (PER) gives an effect of 58.2% and the remaining 41, 8% were influenced by other variables.Keyword: return on asset (ROA), price earning ratio (PER), stock prices